The importance of the criteria of residential buildings from the perspective of future users - Sirochmanová Lenka; Kozlovská Mária; Bašková Renáta (Selected Scientific Papers: Journal of Civil Engineering, 2016)
The developers need to know what is important to their customers in preparation of new construction of residential buildings. The paper deals with finding the importance of structure, material, cost, time and environmental criteria of residential buildings from the perspective of the future owners. The research methodology that provided the information was questionnaire survey. Research was conducted in two lines. The first line is dedicated to the research of main construction domains of residential building. The second line of the research deals with the specific criteria of main construction domains. The order of importance of the main areas and the specific criteria is determined by analyzing of data through descriptive characteristics: median, modus, variance, average value and by weigh of importance.